Flipped classroom for music theory course in Chinese universities: a conceptual framework of practice - Zhu, Qisen; Jamaludin, Khairul Azhar; Nasri, Nurfaradilla Mohamad; Li, Jinglong (Cogent education, 2025)
Music theory is a vital but challenging subject for students, often leading to low engagement and understanding. Flipped Classroom (FC), combining blended learning, self-directed learning, and collaboration, is increasingly used to address these issues. Its application is important for improving learning effectiveness and supporting diverse student needs. This study proposes the Flipped Classroom Self-Directed Learning (FCM) module, integrating self-directed learning (SDL) with flipped classroom pedagogy to enhance music theory education. Addressing the research gap in combining these approaches, the module aims to cultivate students' critical thinking, problem-solving skills, and self-management capabilities through systematic instructional design. Employing literature review and case analysis methodologies, the research emphasizes two core implementation elements: 1) establishing clear learning objectives and structured plans to guide flipped classroom activities, and 2) enhancing teachers' pedagogical-technological competencies to facilitate SDL processes. Findings reveal that the FCM module effectively stimulates learning motivation while improving theoretical comprehension and application skills. The organic integration of SDL components addresses common deficiencies in student autonomy within flipped classroom environments, demonstrating significant potential for optimizing learning outcomes. This research contributes to educational innovation by providing an implementable framework that synergizes blended learning paradigms with self-regulated learning strategies in music instruction.